Finite Element Analysis on Pelvis With Leg Length Inequality - Othman, N. F.; Tan, H. Y.; Basaruddin, K. S.; Som, M. H. Mat; Rusli, W. M. R.; Sulaiman, A. R. (International Journal of Engineering and Technology, 2018)
Leg length inequality, also known as leg length discrepancy (LLD) is a condition which the left and right legs of an individual are noticeably different in length. When the level of LLD is high, such as those of 20 mm and above, it would disturb the wellbeing of an individual in terms of gait, and also causes them to experience higher stress in their pelvis compared to individual without LLD. In order to study load due to LLD had affects human bones such as the pelvic bone, finite element analysis (FEA) approach is usually used as it allows limitless attempt to investigate the stress-strain response on human bones and is far more practical than experimenting on real bones, therefore FEA was done with by using ANSYS 15.0. From the data obtained via FEA, the risk of fracture can be calculated, which gives us an insight on how would LLD affects the risk of bone fracture. In this study the effect of pelvic tilt caused by LLD has been studied, along with how loads at various LLD level affects the pelvic bone. The verdict from the study is the pelvic tilt caused by LLD amplifies the maximum stress and strain on the pelvic bone. The analysis using hip load due to LLD shows a downtrend for the maximum stress caused by the longer limb as the level of LLD increases, while the maximum stress caused by the shorter limb shows an uptrend with the increment of LLD. The maximum stress and strain observed are usually distributed around the sacroiliac joint. It is also observed that the higher the level of LLD is, the higher the maximum stress on pelvic bone will become, hence the higher the fracture risk.